The sons of Muqrin al-Muzani, a historical study (Journal of the College of Basic Education, 2022)
Praise be to God, the Lord of the Worlds 0, and prayers and peace be upon the master of the Messengers; Muhammad the Seal of the Prophets 0 and his wivesThe Mothers of the Believers + and his good and pure family 0 and his honest and sincere companions.But after wSo he taught the knowledge of the Companions, may God be pleased with them, for the sake of science, as it came from Al-Hafiz Ibn HajarAl-Asqalani L. The reason for this is that the Companions, may God be pleased with them; They are the ones who moved astrayThe two foundations, the two texts, and the two revelations are the Great Qur’an and the venerable Sunnah. Understanding the witnesses, the campaign, the transfer, and the narratorsThat's who.The Qur’an stipulates that they are recommended, modified, and documentedOtherwise.Because of this importance, this research was invented and named: (The Sons of Muqrin Al-Muzani, a Historical Study).